1958
DOI: 10.2307/3893670
|View full text |Cite
|
Sign up to set email alerts
|

Grazing Preference Comparisons of Six Native Grasses in the Mixed Prairie

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1964
1964
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Observations indicate that some species are grazed heavily when they occur in small quantities throughout a "better" forage, whereas in dense stands the use is light. This has been reported for Artemisia tridentata (Stoddart and Smith, 1955), Ceanothus t hyrsiflorus (Hooper, 1962) and Agropyron simithii on lowland sites (Tomanek et al, 1958). Preference in relation to differences in species composition on one habitat was studied by Heady and Tore11 (1959).…”
Section: Facfors Inf Iuencing Relative Preferencementioning
confidence: 71%
“…Observations indicate that some species are grazed heavily when they occur in small quantities throughout a "better" forage, whereas in dense stands the use is light. This has been reported for Artemisia tridentata (Stoddart and Smith, 1955), Ceanothus t hyrsiflorus (Hooper, 1962) and Agropyron simithii on lowland sites (Tomanek et al, 1958). Preference in relation to differences in species composition on one habitat was studied by Heady and Tore11 (1959).…”
Section: Facfors Inf Iuencing Relative Preferencementioning
confidence: 71%
“…However, the quadratic slope for all species was 0.17 cm per 2‐wk period, resulting in a grass height increase over time for IG but in height decreases for both bluestems. Preferential grazing of LB and BB by cattle over other NWSG has been documented on native range in the Great Plains (Fahnestock & Knapp, 1993; Hartnett, Hickman, & Walter, 1996; Tomanek, Martin, & Albertson, 1958), but this may be the first time it has been documented in planted mixed NWSG pasture.…”
Section: Resultsmentioning
confidence: 99%
“…Rogler (1944) reported that warm-season grasses were, in general, more highly relished by steers than cool-season grasses. Tomanek et al ( 1958) determined that big bluestem (Cd) (Andropogon gerardii) and little bluestem (Cd) (Schizachyrium ~coparium) had a significant positive preference by grazing cattle wherever they occurred, while preference for western wheatgrass (C,) (Agropyron smithii) varied with site. This indicates that a generalization concerning lower palatability of Ca species compared to CJ may not apply to all herbivores.…”
Section: Adaptation and Competitionmentioning
confidence: 99%